2015
DOI: 10.1111/jsm.13021
|View full text |Cite
|
Sign up to set email alerts
|

Low Quality of Life and Depressive Symptoms as an Independent Risk Factor for Erectile Dysfunction in Patients with Obstructive Sleep Apnea

Abstract: Introduction Accumulating evidence indicates that obstructive sleep apnea (OSA) is associated with a high prevalence of erectile dysfunction (ED), but the factors that predict the risk of ED in OSA patients have yet to be defined clearly. Aims The aims of the present study were to investigate the clinical characteristics of OSA patients with ED and to identify plausible predictors of ED. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…On the other hand, some studies reported that OSA or nocturnal hypoxemia was not associated with ED. 25,46 Yung et al 25 analyzed data from 713 male patients who underwent full-night PSG monitoring and found that the frequency of ED did not differ significantly according to OSA severity and there was no significant association of ED with either the AHI or lowest SaO2. The possible reasons for the discrepancies between our findings and some previous studies are as follows: (i) The exclusion criteria were different.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, some studies reported that OSA or nocturnal hypoxemia was not associated with ED. 25,46 Yung et al 25 analyzed data from 713 male patients who underwent full-night PSG monitoring and found that the frequency of ED did not differ significantly according to OSA severity and there was no significant association of ED with either the AHI or lowest SaO2. The possible reasons for the discrepancies between our findings and some previous studies are as follows: (i) The exclusion criteria were different.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study by Yung Jin Jeon et al showed that the frequency of ED did not differ significantly according to OSA severity, and there was no significant association of ED with either the respiratory disorder index (RDI) or lowest SaO 2 . 25 Based on these considerations, we used comprehensive PSG data in a large sample of patients suspected to have OSA to assess whether those parameters including RDI (or AHI), lowest SaO2, mean SaO2, SIT90%, ODI, obstructive apnea index (OAI), maximum apnea time, microarousal index, oxygen reduction frequency (ORF), maximum oxygen reduction (MOR), longest oxygen reduction time (LORT), central apnea frequency, and obstructive apnea frequency were related to ED. In addition, we propose a new calculation method, the blood oxygen accumulation distribution area index (BOADAI), which integrates the information of apnea events and nocturnal hypoxemia to evaluate the association between OSA and ED.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown a high incidence of ED among male OSA patients, ranging from 47.1% to 80.0% [2021222324]. The severity of OSA is considered to be an important factor in the development of ED [2526], however, this finding is not consistent [27]. A Korean study by Shin et al [28] showed that ED is associated with decreased minimum oxygen saturation, not with AHI.…”
Section: Main Bodymentioning
confidence: 99%
“…The risk for sleep apnea increases with age and occurs at a higher frequency in men than women [46]. Male sexual dysfunction is commonly associated with sleep apnea and can greatly lower quality of life [7, 8].…”
Section: Introductionmentioning
confidence: 99%